Long-term outcomes of pulmonary atresia with ventricular septal defect by different initial rehabilitative surgical age - Ma, Jianrui; Tan, Tong; Zhang, Shuai; Xie, Wen; He, Yinru; Tian, Miao; Tujia, Zichao; Li, Xinming; Liu, Xiaobing; Chen, Jimei; Zhuang, Jian; Cen, Jianzheng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background There is a lack of evidence guiding the surgical timing selection in pulmonary atresia with ventricular septal defect. This study aims to compare the long-term outcomes of different initial rehabilitative surgical ages in patients with pulmonary atresia with ventricular septal defect (PAVSD). Methods From January 2011 to December 2020, a total of 101 PAVSD patients undergoing the initial rehabilitative surgery at our center were retrospectively reviewed. Receiver-operator characteristics curve analysis was used to identify the cutoff age of 6.4 months and therefore to classify the patients into two groups. Competing risk models were used to identify risk factors associated with complete repair. The probability of survival and complete repair were compared between the two groups using the Kaplan-Meier curve and cumulative incidence curve, respectively. Results The median duration of follow-up was 72.76 months. There were similar ΔMcGoon ratio and ΔNakata index between the two groups. Multivariate analysis showed that age ≤6.4 months (hazard ratio (HR) = 2.728; 95% confidence interval (CI):1.122–6.637; p = 0.027) and right ventricle-to-pulmonary artery connection (HR = 4.196; 95% CI = 1.782–9.883; p = 0.001) were associated with increased probability of complete repair. The cumulative incidence curve showed that the estimated complete repair rates were 64% ± 8% after 3 years and 69% ± 8%% after 5 years in the younger group, significantly higher than 28% ± 6% after 3 years and 33% ± 6% after 5 years in the elder group (p < 0.001). There was no significant difference regarding the estimated survival rate between the two groups. Conclusion Compared with those undergoing the initial rehabilitative surgery at the age >6.4 months, PAVSD patients at the age ≤6.4 months had an equal pulmonary vasculature development, a similar probability of survival but an improved probability of complete repair.